Anti-Inflammatory Activity and Structure-Activity Relationships of Brominated Indoles from a Marine Mollusc - Ahmad, Tarek B. (Mar Drugs, 2017)
Marine molluscs are rich in biologically active natural products that provide new potential sources of anti-inflammatory agents. Here we used bioassay guided fractionation of extracts from the muricid Dicathais orbita to identify brominated indoles with anti-inflammatory activity, based on the inhibition of nitric oxide (NO) and tumour necrosis factor α (TNFα) in lipopolysaccharide (LPS) stimulated RAW264.7 macrophages and prostaglandin E2 (PGE2) in calcium ionophore-stimulated 3T3 ccl-92 fibroblasts. Muricid brominated indoles were then compared to a range of synthetic indoles to determine structure-activity relationships. Both hypobranchial gland and egg extracts inhibited the production of NO significantly with IC(50) of 30.8 and 40 μg/mL, respectively. The hypobranchial gland extract also inhibited the production of TNFα and PGE2 with IC(50) of 43.03 µg/mL and 34.24 µg/mL, respectively. The purified mono-brominated indole and isatin compounds showed significant inhibitory activity against NO, TNFα, and PGE2, and were more active than dimer indoles and non-brominated isatin. The position of the bromine atom on the isatin benzene ring significantly affected the activity, with 5Br > 6Br > 7Br. The mode of action for the active hypobranchial gland extract, 6-bromoindole, and 6-bromoisatin was further tested by the assessment of the translocation of nuclear factor kappa B (NFκB) in LPS-stimulated RAW264.7 mouse macrophage. The extract (40 µg/mL) significantly inhibited the translocation of NFκB in the LPS-stimulated RAW264.7 macrophages by 48.2%, whereas 40 µg/mL of 6-bromoindole and 6-bromoistain caused a 60.7% and 63.7% reduction in NFκB, respectively. These results identify simple brominated indoles as useful anti-inflammatory drug leads and support the development of extracts from the Australian muricid D. orbita, as a new potential natural remedy for the treatment of inflammation.